The lexical-semantic and functional-stylistic peculiarities of military vocabulary in P. Zagrebelnyi’s novel “Roxolana” (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2010)
The semantic, functional and stylistic peculiarities of military vocabulary in P. Zagrebelnyi’s novel “Roxolana”. The article deals with the increasing process of semantic structure of the military vocabulary that expands its functional area.
Keywords: military vocabulary; semantic structure; nominative function